COMPARATIVE STUDY BETWEEN PHYTOGENIC AND ESCHERICHIA COLI VACCINE IN BROILERS - Abdullah , S.M.; Abdulmaged, Sahar.H.; Hamad, S.M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
The present study carried out to comparative between usage of killed vaccine of Escherichia coli with aromatic oils or alone against infection of broiler with pathogenic E.coli for this purpose two hundred broiler chicks were collected and randomly divided into four groups. Each group contained fifty chicks, food and drink for all groups ad libitium. The experimental groups were treated as follows: G1 vaccinated with the killed E. coli vaccine through subcutaneous injection dose 0.5 ml (3×107 CFU/ml )in day five old and received Digestarom® P.E.P sol. in drinking water 6 ml/100L from one day old until end of trial. G2 vaccinated with killed E. coli only through subcutaneous injection dose 0.5 ml (3×107 CFU/ml) in day five old. G3 received Digestarom® P.E.P sol. in drinking water 6 ml/100Lonly one day old until end of trial. G4 control negative. The experimental birds in day 25 were challenged intratracheally inculated with Escherichia coli of 0.5 ml was LD50(3 ×108 CFU/ml) in the experiment. Blood samples were taken at day 20 and 35 for assessment of different parameters, mortality and lesions score were determined . The results showed that the use of aromatic oils and received killed vaccine of E.coli has a good effect on the immune response , decreasing the mortality rate and lesion score of E. coli infected chickens. It can be concluded from the current study that the use digestarom enhancement the immune response after vaccination with E.coli vaccine against pathogenic E.coliIt also the use E.coli vaccine with the digestarom in broiler chickens is more effective than using the vaccine alone